Differences in Premenopausal Syndrome Between Users of Hormonal and Non-Hormonal Contraceptive Methods (Wahana : Tridarma Perguruan Tinggi, 2025)
Premenopause, menopause, and postmenopause are three phases that women will experience when they are aged 40 to 50 years. The menopause phase is usually preceded by the premenopause phase. This study aims to determine the difference in premenopause syndrome between hormonal and non-hormonal contraceptive acceptors. The research design used was an analytic survey research design with a cross-sectional approach. The number of samples in this study was hormonal and non-hormonal contraceptive acceptors, selected using purposive sampling. The data analysis used was the Paired Sample t-Test. The results showed that the majority of hormonal contraceptive acceptors were in the "no premenopause syndrome" category, totaling 18 respondents (78.3 percent, and the "mild" category, totaling 5 people (21.percent). For non-hormonal contraceptive acceptors, the "no" and "moderate" categories each had 4 respondents (17.4 percent), the "mild" category had 13 respondents (56.5 percent), and the "severe" category had 2 respondents (8.7 percent). With the independent sample t-test $p$-value (0.043 is less than 0.05), H0 is rejected, meaning there is a difference in premenopause syndrome between hormonal and non-hormonal contraceptive acceptors at, Tajinan sub-district. Based on the research results, it can be concluded that there is a significant difference in premenopause syndrome between hormonal and non-hormonal acceptors. Therefore, health workers can provide education regarding ways to overcome premenopause syndrome and encourage contraceptive acceptors to adopt a healthy lifestyle and exercise regularly.